Research on Ideological and Political Teaching Reform of Basic Course of Mechanical Design in Higher Vocational Colleges (Contemporary Education and Teaching Research, 2023)
In the context of the new situation, the course of political thinking for higher vocational schools is a new teaching concept, which requires higher vocational schools in the teaching of basic mechanical design must be based on the characteristics of the course itself and the culture of the discipline, to take up the task of educating their own, and at the same time, the professional course teachers need to take up the responsibility of educating the people, and to maximize the potential political thinking in the basic mechanical design course to dig out the potential political thinking, and effectively implement the requirements of the moral and humane education. Effectively implement the requirements of moral education. In the process of the change of the basic mechanical design professional course civics teaching, it is necessary to build a "full staff education, all-round education and the whole process of education and teaching pattern, strengthen the course of civics education, and further improve the "island" like education predicament. In addition, senior teachers also need to sort out and integrate the cultural and educational factors related to civics and politics, combined with the professional content of the basic mechanical design, to strengthen the practice and exploration of the basic mechanical design profession, and to broaden the career prospects of higher vocational students.